Lumbar spondylolysis in competitive diving athletes ~case series~ - Tatsumura, M.; Asai, R.; Tsukagoshi, Y. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Lumbar spondylolysis is a fatigue fracture of the pars interarticularis of the lumbar vertebral arch and is common in adolescent athletes. Lumbar spondylolysis is also the most common identifiable cause of low back pain in young athletes and the main symptom of it is low back pain during exercise. The first line of treatment is conservative therapy, which includes rest and a brace. The incidence of spondylolysis has been shown to be 6% in the general adult population and the incidence is higher in the athletic population, with studies showing as many as 52% of athletes with low back pain suffering spondylolysis. Lumbar spondylolysis is also reported to be common in gymnastics, where the movements are similar to those of diving. In the present study, we investigated the trend of lumbar spondylolysis in competitive divers and its relationship to competition, using three cases of early-stage lesions in our experience.